Use of epidemiological publications among health professionals. - Chandrasekar, K.; Bath, P.A. (Sri Lanka Library Association, 2010)
Abstract In today’s world, information is considered one of the basic resources. As a source of information, publications play an important role in any discipline. In relation to infectious disease surveillance, Weekly Epidemiological Report (WER) and Quarterly Epidemiological Bulletin (QEB) published by the Epidemiology unit are considered the chief source of current epidemiological information in Sri Lanka. This study was carried out among health staff engaged in notifiable disease surveillance activities in Jaffna District (Sri Lanka). A qualitative approach, using in-depth semi-structured interviews, was chosen to collect information about their perception of and problems with these epidemiological publications. Based on the information collected through these interviews, significance of these epidemiological publications, awareness and utilization of these publications among health staff, quality of published information and influence of these publications on policy decisions were analysed. Primarily, these publications are published to serve the purpose of disseminating epidemiological information related to Sri Lanka. However, their impact is not satisfactory. This study revealed that limited circulation of these publications is one of the reasons for poor impact. In Jaffna, only 25% of the medical institutions, namely government hospitals with in-patient care facilities in the western medical system, RDHS office, MOH offices and medical library at the Faculty of Medicine, University of Jaffna, are getting these publications. None of the traditional medical institutions, western medical institutions in the private sector and primary healthcare units in the government sector are supplied with these publications. Further, public health inspectors are the field level staff, who are involved in prevention and control of infectious diseases, are also not getting these publications. This results in lack of awareness about epidemiological information among health staff of Jaffna. Apart from awareness, factors such as problems in accessibility, time delay in publication and medium as a barrier for utilization are also contributing to the poor utilization of these publications among health professionals. Ninety percent of the participants of this study are satisfied with the quality of information provided in these publications. Whereas, it was felt that extent of utilization of surveillance statistics in policy decision making is not satisfactory. Hence, it is recommended that adequate efforts should be taken at national level to ensure the timeliness of release and accessibility of these epidemiological publications, in order to improve the utilization among health professionals at local level. Further, dissemination of this health information to the general public through health education programmes should be the responsibility of the regional and local health authorities. Further, initiatives should be taken at regional level to collect, collate and publish epidemiological information at regular intervals. In addition, maintaining a website at regional level with health sector issues (including disease surveillance details) pertaining to that particular region, would also enhance the accessibility of epidemiological information. X---------------------------------X